Changing Antiretroviral Eligibility Criteria: Impact on the Number and Proportion of Adults Requiring Treatment in Swaziland. (1st March 2016) - Bock, Naomi N.; Emerson, Ruth C.; Reed, Jason B.; Nkambule, Rejoice; Donnell, Deborah J.; Bicego, George T.; Okello, Velephi; Philip, Neena M.; Ehrenkranz, Peter D.; Duong, Yen T.; Moore, Janet S.; Justman, Jessica E.
Abstract : Objective: Early initiation of antiretroviral treatment (ART) at CD4 + cell count ≥500 cells per microliter reduces morbidity and mortality in HIV-infected adults. We determined the proportion of HIV-infected people with high viral load (VL) for whom transmission prevention would be an additional benefit of early treatment. Design: A randomly selected subset of a nationally representative sample of HIV-infected adults in Swaziland in 2012. Methods: Eight to 12 months after a national survey to determine adult HIV prevalence, 1067 of 5802 individuals identified as HIV-infected were asked to participate in a follow-up cross-sectional assessment. CD4 + cell enumeration, VL measurements, and ART status were obtained to estimate the proportion of currently untreated adults and of the entire HIV-infected population with high VL (≥1000 copies/mL) whose treatment under a test-and-treat or VL threshold eligibility strategy would reduce HIV transmission. Results: Of the 927 (87% of 1067) participants enrolled, 466 (50%) reported no ART use. Among them, 424 (91%) had VL ≥1000 copies per milliliter; of these, 148 (35%) were eligible for ART at the then existing CD4 + count threshold of <350 cells per microliter; an additional 107 (25%) were eligible with expanded CD4 + criterion of <500 cells per microliter; and 169 (40%) remained ART ineligible. Thus, 36% of the 466 currently untreated and 18% of the total 927 had high VL yet remained ART ineligible under a CD4 + criterion of <500 cells per microliter. Conclusions: A test-and-treat or VL threshold for treatment eligibility is necessary to maximize the HIV transmission prevention benefits of ART.